Antioxidant Activities and Cytotoxicity Effect on Normal Human Dermal Fibroblasts of Roselle (Hibiscus sabdariffa L.) Calyces Extracts and W/O/W Emulsion Loaded Extract for Cosmetic Applications - Itsarasook, Khwunjit; Prompamorn, Piyanuch; Tanghiranrat, Jittarawadee; Chantree, Kanlayaporn; Itsarasuk, Itsaret (Journal of Food Health and Bioenvironmental Science, 2023)
The objective of this study was to evaluate the antioxidant activities and cytotoxicity effect on normal human dermal fibroblasts of roselle (Hibiscus sabdariffa L.) calyx extracts and to load with the roselle extract in the inner phase of water in oil in water multiple emulsion for application in facial cosmetic. The extracts of dried roselle calyces were prepared by a maceration technique using ethanol/water at concentrations of 30%, 70%, 95% and 0% (100% DI water). Obtained results showed that the 30% ethanolic extract had a higher amount of total phenolic and anthocyanin content than other extracts. According to the DPPH and ABTS assays, the 30% ethanolic extract exhibited dose-dependent antioxidant activity higher than other extracts with an IC50 value of 0.432±0.001 mg/mL and 0.0855±0.01 mg/mL, respectively. The formulation of water in oil in water multiple emulsion containing the roselle calyx extract was prepared by a beaker method with twostep emulsification. The prepared multiple emulsion showed a light pink color with homogeneously formula. The physiochemical stability of the prepared formula was evaluated at accelerated conditions; room temperature (30±5ºC), low temperature (4±1ºC) and high temperature (40±1ºC) for 30 days and 6 cycles of freeze (-25ºC, 24 h)-thaw (4ºC, 24 h). Results found that the tested formula showed a good physicochemical stability compared to the initial condition. All finding suggests possible application for the 30% ethanolic extract of roselle calyces as a natural active ingredient in skin cosmetic products.